Analysis Of The Implementation Of The Salam Agreement (PSAK Syariah 103) In E-Commerce Shopee - Ramaditya Khadifa; Devi Astriani; Meliana Puspitasari (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — This research aims to analyze the implementation of salam contracts based on PSAK Syariah on the Shopee e-commerce platform, focusing on user understanding and transaction practices. Research method— A descriptive method with a qualitative approach was employed, utilizing direct observation and interviews with sellers and buyers on the Shopee platform Result— The findings indicate that many Shopee users are unaware of salam contracts; however, those who do engage in transactions meet the necessary requirements and maintain harmonious buying and selling practices Conclusion— The study concludes that while awareness of salam contracts is limited, users are capable of fulfilling contractual obligations. This highlights the need for improved education on salam contracts within the e-commerce context to enhance user